EKSPLORASI KIMONO DENGAN PERPADUAN BATIK - ANNEIRA CERWYN RIADY; HANNA QOLBUNAL IMANI; RANIA SABILA (Fashion and Fashion Education Journal, 2023)
Fashion or clothing style is one of the daily needs of humans that has existed since ancient times, hence there are many traditional costumes such as kimono from Japan and batik from Indonesia. Each of these costumes has been recognized as a world heritage in 2009. In the present day, kimono and batik have become one of fashion creations that are developed without eliminating the philosophy behind each costume. This research uses descriptive qualitative research with a literature and library study approach. The results of this research develop a combination of kimono and batik as one of the current fashion creations without eliminating their philosophy